The Kleczew enclave of the Kujavian long barrows. An overview - Gorczyca, Krzysztof (Folia Praehistorica Posnaniensia, 2018)
The article is aimed at general overview o f the long barrows o f the Funnel Beaker Culture discovered in the Kleczew vicinity, Konin district. These tombs are largely destroyed and thus presented analysis is mostly based upon archive materials. According to accounts from the early half of the 19th century, there were 150 tombs in this area. Only 22 of them can be localised at present.